Rare coral and reef fish species status, possible extinctions, and associated environmental perceptions in Mauritius. Issue 11 (3rd September 2021) - McClanahan, Tim; Munbodhe, Vikash; Naggea, Josheena; Muthiga, Nyawira; Bhagooli, Ranjeet
Abstract: Mauritius is reported to have the highest marine species endemism in the Western Indian Ocean faunal Province but the status of these species has not been evaluated. To address this knowledge gap, 119 reef sites were sampled to evaluate populations of 16 species of rare and endemic reef fish and corals using scuba‐based surveys conducted by citizen scientists and marine science professionals. Additionally, we interviewed ~1, 000 households in 27 coastal villages to determine their perceptions of the environmental concerns and rare and endemic marine species. In general, population numbers of both studied corals and fish were low and distributions were patchy, with little indication that the fisheries management zones were protecting these species. The Mauritian gregory and Mauritian anemonefish were the most abundant species. The Mauritian and Creole damselfishes, which are range‐restricted Mascarene endemics, were not observed and potentially extinct. Endemic fish and coral population numbers were higher on the leeward than windward side of the island. The leeward side has higher tourism use and conservation activities that could promote endemic conservation. Environmental concerns of interviewees were high but varied by district and their socioeconomic contexts. Respondents showed an overall concern for the environment and agreed that endemic and rare species had a right to survive. Nevertheless, these rare and endemic coral reef species are threatened by isolation and habitat loss combined with rapid climate and human resource use change. National and district‐specific plans of actions could help to secure their futures.